Exploring the practicality of transition care guidance for paediatric CHD patients: a case series - Panda, Shramana Ray; Shetty, Asha P.; Dwibedi, Bhagirathi (International Journal of Research in Medical Sciences, 2025)
This pilot study evaluates the feasibility of implementing a nurse-led transition care program among caregivers of CHD children admitted to a pediatric medicine ward. A quantitative approach was used to collect the data from eight caregivers and children distributed equally among control and experimental group. The study has used data collection instruments including demographic proforma, caregiver’s knowledge and self-efficacy format as well as satisfaction form. Results highlighted the feasibility of implementing a nurse-led transition care program in pediatric patients and showed the potential benefit of a nurse-led program in terms of improved caregiver readiness for discharge. Study findings provide a base for implementing structures and transition care models to improve post-transition healthcare outcomes.